Development Of Futsal Playing Skills Application Based On Web-Based Futsal Analysis System (FAST) - Mochamad Ridwan; Muhammad Dzul Fikri; I Dewa Made Aryanandha; Imam Syafi"i; Arif Bulqini (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2021)
This study aims to determine the level of success of futsal athletes in applying playing skills. This research was conducted at the Unesa Futsal GOR with a sample of 25 athletes from the Unesa Women's Futsal UKM. The method used in this research is Waterfall Methods. This method is a Software Development Life Cycle (SDLC) approach. The results of this study are the FAST application can display graphs and the percentage of success, failure of athletes in carrying out basic technical movements. It can be concluded that the FAST application is suitable for use by coaches to determine futsal playing skills.